2015
DOI: 10.3892/mmr.2015.3357
|View full text |Cite
|
Sign up to set email alerts
|

Repression of metadherin inhibits biological behavior of prostate cancer cells and enhances their sensitivity to cisplatin

Abstract: Metadherin (MTDH), also known as astrocyte-elevated gene-1, was first cloned in 2002 and has been confirmed as an oncogene in numerous types of cancer by previous studies. Overexpression of MTDH has been observed in multiple types of cancer, including breast, esophageal, prostate, cervical and non-small-cell lung cancer, as well as neuroblastoma and hepatocellular carcinoma. However, at present, few investigations into MTDH-associated prostate cancer have been performed. A previous study suggested that MTDH wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…This approach induced a CD8+ T cell-mediated immune response inhibiting tumor growth and metastasis and increased the chemosensitivity to paclitaxel with a prolongation of the survival time [ 237 ]. The inhibition of AEG-1 in prostate cancer cells increased the sensitivity to cisplatin through modulating the PI3K/AKT pathway [ 238 ].…”
Section: Role Of Aeg-1 In Cancer Drug Resistancementioning
confidence: 99%
“…This approach induced a CD8+ T cell-mediated immune response inhibiting tumor growth and metastasis and increased the chemosensitivity to paclitaxel with a prolongation of the survival time [ 237 ]. The inhibition of AEG-1 in prostate cancer cells increased the sensitivity to cisplatin through modulating the PI3K/AKT pathway [ 238 ].…”
Section: Role Of Aeg-1 In Cancer Drug Resistancementioning
confidence: 99%
“…Growing evidence reveals that AEG-1 is significantly related to the invasion, migration, apoptosis and prognosis of different cancers, such as hepatocellular carcinoma [9], bladder cancer [10], prostate cancer [11], gastric cancer [12] and so on. Zhou et al [9] found that AEG-1 was highly expressed in high metastatic potential cancer cell lines and the AEG-1 expression was positively correlated with orientation chemotaxis and adhesion of human hepatocellular carcinoma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [9] found that AEG-1 was highly expressed in high metastatic potential cancer cell lines and the AEG-1 expression was positively correlated with orientation chemotaxis and adhesion of human hepatocellular carcinoma cell lines. Wei et al [11] found that AEG-1 could act as an oncogene and the inhibition of AEG-1 expression could promote cell apoptosis, reduce cell viability and weaken the invasive ability of prostate cancer cells. In addition, the suppression of AEG-1 expression could improve the cell sensitivity to cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, MTDH may inhibit the expression of cell cycle protein inhibitors, including p53, p21 and p27 and induce the expression of cell cycle promoting proteins, including cyclin D1 and cyclin E (37). In prostate cancer, the inhibition of MTDH promoted apoptosis, reduced cell viability and increased cell sensitivity to cisplatin (38). MTDH may also promote human cancer growth by regulating the expression of specific miRNAs (39).…”
Section: Discussionmentioning
confidence: 99%